A holistic approach for selection of Bacillus spp. as a bioremediator for shrimp postlarvae culture. - Devaraja, Thimmalapura; Banerjee, Sanjoy; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff; Khatoon, Helena (Scientific and Technological Research Council of Turkey, 2013)
Indigenous Bacillus pumilus, B. licheniformis, and B. subtilis were isolated from marine water and soil samples and investigated for potential bioremediation ability in Penaeus monodon culture. Bacillus spp. were selected based on their wide range of growth conditions, ease of mass culture, tolerance to total ammonia nitrogen (TAN), inhibition of pathogenic vibrios, nonpathogenicity, and ability to reduce TAN. Results showed that optimum growth of the selected Bacillus spp. occurred at 30 Â°C, pH 7.5, and 1.5% NaCl, and they secreted protease, amylase, and lipase. Vibrio spp. were also inhibited by 3 Bacillus spp. In addition, the selected Bacillus spp. had no pathogenic effect on shrimp postlarvae (PL) and were able to reduce TAN. They promoted better growth and survival in shrimp PL without water exchange. This study was a systematic approach undertaken for the selection of suitable Bacillus spp. as bioremediators for a Penaeus monodon culture system.